The Effect of Propensity Score Matching Method on the Quantity and Quality of Matches - Jacovidis, Jessica N.; Foelber, Kelly J.; Horst, S. Jeanne (The Journal of experimental education, 2017)
Often program administrators are interested in knowing how students benefit from participation in programs compared to students who do not participate. Such comparisons may be sullied by the fact that participants self-select into programs, resulting in differences between groups prior to programming. By controlling for researcher-identified-self-selection variables, propensity score matching enables researchers to create comparable matched groups. However, when employing propensity score matching, researchers are faced with a plethora of matching options. In the current study, we compared the quantity and quality of matches obtained when applying common matching techniques to real data. The methods produced matches of varying quantity and quality. Moreover, group comparisons on the outcome led to different conclusions depending on the matching method employed.